Gastrointestinal Morbidity in Obesity - Acosta, Andres (2014)
Obesity is a complex disease that results from increased energy intake and decreased energy expenditure. The gastrointestinal system plays a key role in the pathogenesis of obesity and facilitates caloric imbalance. Changes in gastrointestinal hormones and the inhibition of mechanisms that curtail caloric intake result in weight gain. It is not clear if the gastrointestinal role in obesity is a cause or an effect of this disease. Obesity is often associated with type 2 diabetes mellitus (T2DM) and cardiovascular diseases (CVD). Obesity is also associated with gastrointestinal disorders, which are more frequent and present earlier than T2DM and CVD. Diseases such as gastro-esophageal reflux disease, cholelithiasis or non-alcoholic steatohepatitis are directly related to body weight and abdominal adiposity. Our objective is to assess the role of each gastrointestinal organ in obesity and the gastrointestinal morbidity resulting in those organs from effects of obesity.